Microwave Assisted Synthesis of ethyl-quinolon-4-one-3-carboxylates and Hydrolysis to quinolon-4-one-3-carboxylic Acids - Malvacio, Ivana (2014)
A fast and efficient microwave assisted synthesis of several ethyl-quinolon-4-one-3-carboxylates and quinolon- 4-one-3-carboxylic acids has been developed. The 3-carboethoxy quinolones are easily obtained in a one-pot procedure through the cyclization of aminomethylenemalonate intermediates obtained by reaction of different p-substituted anilines and diethyl-ethoxymethylenmalonate. These quinolones are then irradiated under base hydrolysis conditions to get the carboxylic acids through a very fast and clean approach.